Sound radiation from a lined exhaust duct with lined afterbody - Demír, Ahmet; Rienstra, Sjoerd W. (My University, 2010)
Aft fan noise radiating from a lined bypass exhaust duct with lined afterbody is modelled in a way that allows an analytical solution of generalised Wiener-Hopf type. A preliminary set of numerically evaluated examples, based on the experiments by Tester at al. seem to confirm their conclusions that the beneficial effect of a lined afterbody is mainly found without mean flow. © 2010 by A. Demir and S.W. Rienstra. © 2010 Elsevier B.V., All rights reserved.
16th AIAA/CEAS Aeroacoustics Conference (31st AIAA Aeroacoustics Conference) -- Stockholm -- 82589
Keywords: Afterbody; Analytical solutions; Beneficial effects; Exhaust ducts; Fan noise; Mean flow; Sound radiations; Bypass ratio; Flight dynamics; Aeroacoustics